2021
DOI: 10.1155/2021/6613243
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hydroxyapatite: Green Catalyst for the Synthesis of Pyrroles, Inhibitors of Corrosion

Abstract: Polysubstituted pyrroles have been synthesized in good yields via a four-component one-pot reaction of 1,3-dicarbonyl compounds, amines, aldehydes, and nitroalkanes using natural hydroxyapatite (HAp) as an efficient green catalyst. This strategy provides advantages such as simple experimental and work-up procedures, mild conditions, high selectivity, low cost, high atom economy, and environmental friendliness; it uses a green commercial catalyst and does not require a solvent. The electrochemical behavior of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The reaction is catalyzed by hydroxyapatite (HAp) and generates tetrasubstituted pyrroles under solvent-free conditions. [20] As shown by Li and Gao et al, high speed vibration milling (HSVM) gives 3-acyl pyrroles by the iodine-catalyzed reaction of nitroalkenes with enaminones (Scheme 1B). [21] Zhu et al showed examples of Lewis acid mediated reactions in the course of their work on gold-and silver-catalyzed pyrrole syntheses (Scheme 1C).…”
Section: Template For Synlett Thiemementioning
confidence: 99%
See 1 more Smart Citation
“…The reaction is catalyzed by hydroxyapatite (HAp) and generates tetrasubstituted pyrroles under solvent-free conditions. [20] As shown by Li and Gao et al, high speed vibration milling (HSVM) gives 3-acyl pyrroles by the iodine-catalyzed reaction of nitroalkenes with enaminones (Scheme 1B). [21] Zhu et al showed examples of Lewis acid mediated reactions in the course of their work on gold-and silver-catalyzed pyrrole syntheses (Scheme 1C).…”
Section: Template For Synlett Thiemementioning
confidence: 99%
“…For instance, Louroubi et al published a green four-component one-pot synthesis of pyrroles starting from 1,3-dicarbonyl compounds, amines, aromatic aldehydes, and nitroalkanes (Scheme 1 A). 20 The reaction is catalyzed by hydroxyapatite (HAp) and generates tetrasubstituted pyrroles under solvent-free conditions. As shown by the group of Li and Gao, high-speed vibration milling gives 3-acylpyrroles by an iodine-catalyzed reaction of nitroalkenes with enaminones (Scheme 1 B).…”
Section: Table 1 Influence Of Brønsted Acids On the Add...mentioning
confidence: 99%
“…[5][6][7] Furthermore, solid phosphates such as NP, fluorapatite or hydroxyapatite have been prepared and used as catalysts. [7][8][9][10] To the best of our knowledge, NP has been used for the first time as a support for metal nanoparticles. [7] Due to the important feature of mesoporous materials that allows a high distribution of active centers, mesoporous NP provides a high distribution and dispersion of palladium nanoparticles.…”
Section: Introductionmentioning
confidence: 99%